Ataskaitų generavimo priemonių taikymas bankuose - Zalieckaitė, Laima; Miniotaitė, Indrė (Information & Media, 2011)
Besikeičianti ir sudėtinga išorinė verslo aplinka organizacijas, iš jų ir bankus, verčia aktyviai ir sparčiai reaguoti į rinkos pokyčius, ieškoti naujų galimybių, o tam reikalinga kokybiška ir operatyvi informacija, efektyvios rezultatų pateikimo ir analizės priemonės. Dinamiška rinkos situacija verčia bankus efektyviai valdyti ir vertinti rinkos riziką, t. y. turėti priemonių, leidžiančių įvairiais pjūviais analizuoti informaciją ir valdyti finansinės veiklos rodiklius. Maža to, valdoma įvairialypės informacijos šaltinių gausa lemia, kad duomenys tampa prieštaringi ir netikslūs. Šiame straipsnyje analizuojamas verslo įžvalgos technologijų sudedamosios dalies – ataskaitų generavimo priemonių, kurios padeda priimti efektyvius sprendimus ir sėkmingai spręsti iškylančias verslo problemas, taikymas bankuose.Pagrindiniai žodžiai: verslo įžvalgos technologijos, ataskaitų generavimo priemonės, ekspertinių sistemų technologija, verslo įžvalgos sistemos.Application of Report generation tools to banksLaima Zalieckaitė, Indrė MiniotaitėSummaryThe dynamic market situation is forcing banks to effectively manage and assess market risks, to have means to analyze various aspects of information management and financial performance, considering that the diverse sources of information, results, data are contradictory and inaccurate.The business intelligence technology is a tool that can help solve these problems. The report generation process is a very important tool for business intelligence technology. Bank managers of all levels rely on information in the reports when making business analysis and reports.The report generation process, changes in factor analysis show that a new approach to the environment of the bank accounts of the process generated, is qualitative changes and their implementation measures.Change is largely due to banks’ external environment and internal environment changes in the bank. Banks need a single universal set of data with all employees to analyze the data it required a cut. Unified data environment would allow a precise and clear definition of the data, and not to misinterpretation. Business intelligence systems based on the data storage, installation, and require the bank accounts of the generation business intelligence tools for installation. This would allow existing data to discover new patterns and possibilities to improve their performance.Following a thorough analysis of the reporting and assessment tools, these systems are classified in many ways, this paper reports the authors consists of generating the classification method. Summary of the classification method and the bank employees’ needs, the article defines the generation of reports should be supported by business intelligence system environment.As the report generation tools support a wide business intelligence systems (packages) spectrum are organizations, including banks, faced with problems when buying business intelligence systems. This article is for business intelligence systems, the selection criteria for banks in the environment, a bank employee needs and business intelligence systems vendor survey.According to the criteria of the banks analyzed and most suitable for the SAP BusinessObjects platform. However, to successfully implement a business intelligence system should be to determine which report generation tools will be implemented SAP BusinessObjects environment. It was therefore carried out a reporting tool features SAP BusinessObjects environment analysis and report generation steps up development bank model.Keywords: report generation tools, expert systems’ technology business intelligence systems.